2021
DOI: 10.1038/s41598-021-85026-7
|View full text |Cite
|
Sign up to set email alerts
|

Tert-butylhydroquinone attenuates doxorubicin-induced dysregulation of testicular cytoprotective and steroidogenic genes, and improves spermatogenesis in rats

Abstract: Doxorubicin (DOX) is a broad-spectrum chemotherapeutic drug used in the treatment of cancers. It acts by generating reactive oxygen species in target cells. The actions are, however, not limited to cancerous cells as it attacks healthy cells, killing them. This study investigated the benefits of the antioxidant, tert-butylhydroquinone (tBHQ), on testicular toxicity following DOX therapy. Twenty-four adult male albino rats were assigned randomly into four groups (n = 6), namely: normal control (NC), tBHQ, DOX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
4
13
0
1
Order By: Relevance
“…The results of the DOX group revealed a significant decrease in serum testosterone and testis index value when compared with the control group. These results were in accordance with previous reported results [4], [29]. The antineoplastic agents can disturb Leydig cells directly [30].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results of the DOX group revealed a significant decrease in serum testosterone and testis index value when compared with the control group. These results were in accordance with previous reported results [4], [29]. The antineoplastic agents can disturb Leydig cells directly [30].…”
Section: Discussionsupporting
confidence: 94%
“…Although DOX is a successful cancer chemotherapeutic, side effects limit the clinical utility of DOX-based therapy, including male infertility [4] and hepatotoxicity [3]. The results of the DOX group revealed a significant decrease in serum testosterone and testis index value when compared with the control group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This hypothesis is supported by our previous experiments that showed that MP inhibited α -glucosidase in vitro and improved pancreatic β -cell function, which culminated into increased serum insulin and decreased blood glucose level [ 5 ]. On the other hand, the direct mechanism involves scavenging free radicals, thus complementing endogenous antioxidants, and likely activating Nrf2, which is known to stimulate antioxidant gene expression [ 20 , 21 ]. Our previous experiments showed that MP, which contained large amounts of phenols and flavonoids, significantly inhibited DPPH radical, had ferric ion reducing activity and H 2 O 2 scavenging activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 34 The increased testicular levels of TNF-α and IL-6 in the untreated CP administered rats suggests the instigation of inflammatory related pathways, which corroborates well with previous reports. 40 Antioxidant and anti-inflammatory agents have been illustrated for their protective capabilities against chemotherapy induced testicular toxicities partly or wholly due to their radicals scavenging capabilities and their modulatory roles on oxidative sensitive inflammatory pathways. 5 , 41 The decrease in testicular TNF-α and IL-6 levels following the intragastric administration of EMD suggests an improvement in the testicular proinflammatory mediator status in CP treated rats which corroborates previous reports.…”
Section: Discussionmentioning
confidence: 99%